Conserved G-Quadruplexes Regulate the Immediate Early Promoters of Human Alphaherpesviruses - Ilaria Frasson; Matteo Nadai; Sara N. Richter (Molecules, 2019)
Human Alphaherpesviruses comprise three members, herpes simplex virus (HSV) 1 and 2 and varicella zoster virus (VZV). These viruses are characterized by a lytic cycle in epithelial cells and latency in the nervous system, with lifelong infections that may periodically reactivate and lead to serious complications, especially in immunocompromised patients. The mechanisms that regulate viral transcription have not been fully elucidated, but the master role of the immediate early (IE) genes has been established. G-quadruplexes are non-canonical nucleic-acid structures that control transcription, replication, and recombination in many organisms including viruses and that represent attractive antiviral targets. In this work, we investigate the presence, conservation, folding and activity of G-quadruplexes in the IE promoters of the Alphaherpesviruses. Our analysis shows that all IE promoters in the genome of HSV-1, HSV-2 and VZV contain fully conserved G-quadruplex forming sequences. These comprise sequences with long loops and bulges, and thus deviating from the classic G-quadruplex motifs. Moreover, their location is both on the leading and lagging strand and in some instances they contain exuberant G-tracts. Biophysical and biological analysis proved that all sequences actually fold into G-quadruplex under physiological conditions and can be further stabilized by the G-quadruplex ligand BRACO-19, with subsequent impairment of viral IE gene transcription in cells. These results help shed light on the control of viral transcription and indicate new viral targets to design drugs that impair the early steps of Alphaherpesviruses. In addition, they validate the significance of G-quadruplexes in the general regulation of viral cycles.